Misconceptions Yield Misleading Results. Comment on Wong et al. Comparative Study of Eclipse and RayStation Multi-Criteria Optimization-Based Prostate Radiotherapy Treatment Planning Quality. Diagnostics 2024, 14, 465 - Björn Hårdemark (Diagnostics)
The study by Wong et al [...]